Effects of divalent cations on responses of a sympathetic ganglion to 5-hydroxytryptamine and 1,1-dimethyl-4-phenyl piperazinium - Nash, H.L. (1981)
1 The effects of raising or lowering [Ca(2+)](o) or [Mg(2+)](o) on potential changes evoked by 5-hydroxytryptamine (5-HT) and by the nicotinic agonist, 1,1-dimethyl-4-phenyl piperazinium (DMPP) have been investigated. 2 Changes in membrane potential were measured at the ganglion or in postganglionic axons by the sucrose-gap technique. The ganglionic response to both 5-HT and DMPP was a depolarization followed by an after-hyperpolarization (AH). AH decayed exponentially over most of its time course; the time constant of decay for 5-HT responses was 4.4 ± 0.3 min (mean ± s.e.mean, rate constant 0.23 min(-1)) and that for DMPP responses was not significantly different, being 3.9 ± 0.3 min (rate constant 0.26 min(-1)). 3 Increasing [Ca(2+)](o) to 5.1 or 7.6 mM caused some hyperpolarization of the ganglion, reduced the amplitude of depolarizations evoked by 5-HT by 29% and usually potentiated responses to DMPP (average 12%). Ca-free solutions caused a depolarization of the ganglion, increased the amplitude of depolarizations evoked by 5-HT by 23% and reduced that of depolarizations to DMPP by 32%. [Mg(2+)](o) 12.7 and 25.4 mM caused depolarizations of the ganglion and reduced the amplitude of depolarizations evoked by 5-HT by 34 and 84%, respectively, and those to DMPP by 10 and 75%, respectively. Mg-free solutions or low [Mg(2+)](o) caused a slow depolarization of the ganglion and reduced the amplitude of depolarizations to both 5-HT and DMPP by approx. 20%. Ca/Mg-free solutions produced a slow depolarization of the ganglion, increased the amplitude of depolarizations evoked by 5-HT by 78% and reduced those to DMPP by 58%. 4 Increasing [Ca(2+)](o) reduced the amplitude of AH evoked by 5-HT by 50% and increased that to DMPP by 73%, while prolonging AH duration and increasing the time constant of decay. Ca-free solutions had complex effects on AH evoked by 5-HT, which were increased on average by 116%, and depressed AH evoked by DMPP; in both cases there was a decrease in the time constant of decay. [Mg(2+)](o) 12.7 mM reduced the amplitude of AH evoked by 5-HT more than that evoked by DMPP, and increased the rate of decline of the exponential phase. Low Mg solutions reduced in amplitude the AH evoked by 5-HT by 56% and the AH evoked by DMPP by 38%. The time constant of decay was increased. Ca/Mg-free solutions reduced AH amplitude in both 5-HT and DMPP responses. The effects on time constant are consistent with the generation of AH by an electrogenic sodium pump, the ATP-ase of which is Mg(2+)-dependent and inhibited by Ca(2+). 5 Responses to 5-HT could be recorded from postganglionic axons and consisted of a rapid depolarization, sometimes followed by an AH whose time constant of decay was smaller than that of ganglionic responses. Full dose-response curves in control and test media could be obtained. In Ca/Mg-free solutions, 5-HT depolarizations were potentiated but no significant shift in the curve was observed. 6 It is suggested that divalent cations modulate the coupling between 5-HT receptor and ion channel, an increase in [Ca(2+)](o) reducing the coupling or stabilizing the ion channel in the closed conformation. Ca(2+) and Mg(2+) may compete for the same binding site. This mechanism does not appear to be involved at nicotinic receptors and their related ion channels.